Application of neural network in rare earth separation flow sheets processes with three outlets - Jia, JT; Wu, S; Zhang, YW; Liao, CS; Yan, CH; Oh, J; Pyun, C; Kim, C (INT ACADEMIC PUBL, 2000)
The concept of neural network is introduced to rare earth separations in this paper. The recursive relations and analytical expression for calculating the possible flow sheets and processes are derived in multi-component systems based on trichotomy. As an example, the application of the concept is elucidated in detail in a separation of light rare earths containing La, Ce, Pr, and Nd in HEH(EHP)-HCl system. The results show that this method is beneficial to summarizing and classifying the flow sheets and processes in rare earth separations, and is essential to the optimization of separation flow sheets. It is also valuable to be applied for the separation into group situations and other similar cases too.